Continuous bioreactor production of polyhydroxyalkanoates in Haloferax mediterranei - Parroquin-Gonzalez, Mariana; Winterburn, James (Frontiers in Bioengineering and Biotechnology, 2023)
In this work, the viability of continuous poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) production with controlled composition in Haloferax mediterranei when fed volatile fatty acids is demonstrated. Continuous fermentations showed to greatly outperform batch fermentations with continuous feeding. Operating the bioreactor continuously allowed for PHBV productivity normalised by cell density to increase from 0.29 and 0.38 mg L-1 h-1, in previous continuously fed-fed batch fermentations, to 0.87 and 1.43 mg L-1 h-1 in a continuous mode of operation for 0.1 and 0.25 M carbon concentrations in the media respectively. Continuous bioreactor experiments were carried out for 100 h, maintaining control over the copolymer composition at around 30 mol% 3-hydroxyvalerate 3HV. This work presents the first continuous production of PHBV in Haloferax mediterranei which continuously delivers polymer at a higher productivity, compared to fed-batch modes of operation. Operating bioreactors continuously whilst maintaining control over copolymer composition brings new processing opportunities for increasing biopolymer production capacity, a crucial step towards the wider industrialisation of polyhydroxyalkanoates (PHAs).